a(n) = 2*(a(n-1)) + 5
a(1) = -3
a(2) = 2*(a(2-1)) + 5
= 2*(a(1)) + 5
= 2*(-3) + 5
= -1
Basically, you take the previous value and plug it in the given formula to obtain the next value.
Write the first five terms of the sequence defined by the recursive formula a(n) = 2*(a(n - 1)) + 5 with a(1) = -3
-3, -10, -24, -43, -81
-3, -1, 3, 11, 27
-3, 2, 7, 12, 17
-3, 4, 18, 46, 102
I'm trying to do this the way I've always done them (and gotten them right in the past) but I keep getting it wrong:(
3 answers
haha I just figured it out too and now I feel stupid, but thank you!
B is -3,-1,3.. is correct 100%